PDK1 Regulates Chemotaxis in Human Neutrophils - Yagi, M. (SAGE Publications, 2009)
Phosphoinositide-dependent kinase (PDK1) plays a central role in signal transduction mediated by phosphatidylinositol 3-kinases (PI3K) and regulates cellular functions in neutrophils. Neutrophils from individuals diagnosed with localized aggressive periodontitis (LAP) present an in vivo phenotype with depressed chemotaxis. The aim of this study was to test the hypothesis that PDK1 regulates chemotaxis in neutrophils and is responsible for the abnormal neutrophil chemotaxis LAP. Neutrophil chemotaxis was significantly suppressed by the PDK1 inhibitor staurosporine. When cells were transfected with PDK1 siRNA, there was a significant reduction in chemotaxis, while superoxide generation was not significantly affected. In primary neutrophils from persons with LAP, PDK1 expression and activation levels were significantly reduced, and this reduction was associated with the reduced phosphorylation of Akt (Thr308) and chemotaxis. Analysis of these data demonstrates that PDK1 is essential for the chemotactic migration of neutrophils, and in the absence of PDK1, neutrophil chemotaxis is impaired.